2014
DOI: 10.5424/sjar/2014123-4693
|View full text |Cite
|
Sign up to set email alerts
|

Effect of gender on growth performance, carcass characteristics and meat and fat quality of calves of Avileña-Negra Ibérica breed fattened under free-range conditions

Abstract: The effect of gender (entire males vs females) on growth performance, carcass traits and meat and fat quality of Avileña-Negra Ibérica calves, fattened under free range conditions and supplemented with concentrate, were investigated. The average daily gain, leg width and thorax depth were higher in males than in females. Carcass conformation score, fore-quarter weight and percentage in carcass were higher in males than in females, whereas dressing percentege, loins and flank percentages in carcass and carcass … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
15
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 27 publications
7
15
2
Order By: Relevance
“…While the meat a* (redness) value was not affected by the feeding system, the b* values (yellowness) were impacted, with concentratediets resulting in lower b* values in comparison to forage diets. These results were congruent with those of Daza et al (2014). Several other studies also have noted higher b* values (more yellowness) for subcutaneous fat of cattle raised on forage (Cooke et al, 2004;Duckett et al, 2013;Avilés et al, 2015).…”
Section: Feeding Managementsupporting
confidence: 85%
“…While the meat a* (redness) value was not affected by the feeding system, the b* values (yellowness) were impacted, with concentratediets resulting in lower b* values in comparison to forage diets. These results were congruent with those of Daza et al (2014). Several other studies also have noted higher b* values (more yellowness) for subcutaneous fat of cattle raised on forage (Cooke et al, 2004;Duckett et al, 2013;Avilés et al, 2015).…”
Section: Feeding Managementsupporting
confidence: 85%
“…In the current study, gender had no significant influence on proportion of ∑SFA in intramuscular fat of Anatolian Water Buffalos. The lack of significant differences between male and female animals in terms of ∑SFA was previously observed in cattle from Avileña-Negra Ibérica breed slaughtered at mean weight of 478 kg (Daza et al, 2014) and for cattle from Holstein-Friesian breed slaughtered between 400-600 kg (Holló et al, 2001). On the other hand, adequate intake of n-3 PUFA is important for the maintenance of health and could reduce the risk of chronic and inflammatory diseases (Welch et al, 2010).…”
Section: Meat Fatty Acidsmentioning
confidence: 75%
“…In the majority of previous studies (Węglarz, 2010;Daza et al, 2014), which compared the carcass fatness of male and female farm animals that were slaughtered at similar ages, carcasses of female animals have been reported to have higher fatness than male animals.…”
Section: Carcass Qualitymentioning
confidence: 99%
“…Essien and Adesope (2003) reported that sex has a great effect on the size of N'Dama calf in Southwest Nigeria. Growth performance was affected by gender (males vs females) (Daza et al, 2014). There was a significant relationship between sex and body weight of Ankole and Friesian calves (Lagu et al, 2012).…”
Section: Resultsmentioning
confidence: 97%